CATEGORIZATION OF COMPOUND NOUNS IN KURDISH AND ENGLISH - Mustafa, Sumaya Khalid (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2020)
This paper is concerned with the categorization of compound nouns in Kurdish and English. It compares compound nouns of the two languages according to the prototype theory, applying categorization as a cognitive assumption. The paper attempts to achieve the following goals: first, classifying Kurdish compound nouns using morphological and semantic criteria, listing Kurdish compound nouns according to the prototype theory, showing the structure based on which the relationship between the components of a compound noun is represented, comparing the morphological and semantic relations between the components of compound nouns of Kurdish to those of English. The data of the study on the Kurdish language were collected and analyzed based on the fact that the author is a native speaker of Kurdish. The results show that the morphological structure of compound nouns in Kurdish is more complex than the structure of compound nouns in English though they share some structures. Unlike English, the head in Kurdish compound nouns is not always a noun. The categorization of Kurdish compound nouns is different from English ones; it depends on the nature of the languages and the different perspectives of their users. In both languages, there are compound nouns whose meaning needs encyclopedic knowledge of the speakers to interpret them. This point confirms the assumptions of cognitive linguistics namely simplicity, conventionality, and semanticity.DOI: doi.org/10.24071/llt.2020.230108